CAMPUR KODE PADA PEMAPARAN ANIES BASWEDAN TENTANG BACAPRES 2024 DI i-NEWS TV - WAHYUDI, RANDI; Gusnetti, Gusnetti (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This article uncovers the process of code mixing that occurred in a dialogue conducted by the Former Governor of DKI Jakarta, Anies Baswedan with iNews TV presenter. The purpose of this study is to describe the forms of code mixing, the types of code mixing and the forms of code mixing carried out by Anies Baswedan. The research method applied is descriptive qualitative, namely by listening techniques and recording the results of conversations contained in the research object. The source of the data in this study is the utterances delivered by Anies Baswedan during a dialogue broadcast by iNews TV stations and uploaded to the iNews TV YouTube channel. From the research conducted, there is a phenomenon of code mixing in the dialogue, namely the existence of external code mixing in the form of transitions from Indonesian to English in the form of words, phrases and clauses.